Borderland Stories: Life at the Russian Border - Jenny Jansson; Maria Jansson (Tractus Aevorum, 2014)
This paper details the project ―Borderland Stories,‖ which focuses on national identity in various borderland regions of the Russian Federation. The authors point out that the contradiction between the pronunciation of national identity in the borderlands and the practical aspects of borders makes it particularly exciting to focus on national identity formation and daily life in the borderlands, especially in a huge country, such as the Russian Federation, that borders many different countries. Collection and analysis of the material are being conducted in 2014 and the first results are due for presentation in 2015.